Daily Torpor and Sleep in a Non-human Primate, the Gray Mouse Lemur (Microcebus murinus) - Royo, Julie; Aujard, Fabienne; Pifferi, Fabien (Frontiers in Neuroanatomy, 2019)
Daily torpor is an energy-saving process which evolved as an extension of non-rapid eye movement (NREM) sleep mechanisms. In many heterothermic species there is a relation between torpor expression and the repartition of the different behavioural states of sleep. Despite the presence of sleep during this period of hypothermia, torpor induces an accumulation of sleep debt which results in a rebound of sleep in mammals. We aimed to investigate the expression of sleep-wake rhythms and delta waves during daily torpor at various ambient temperatures in a non-human primate model, the grey mouse lemur (Microcebus murinus). Cortical activity was measured with telemetric electroencephalography (EEG) recordings in prefrontal cortex during torpor episode and the next 24h following hypothermia. Grey mouse lemurs were divided into two groups: the first submitted to normal ambient temperatures (25°C) whereas the second were placed at lower ambient temperatures (10°C). Contrary to normal ambient temperatures, sleep-wake rhythms were maintained during torpor until Tb of the animals reached 21°C. Below this temperature, NREM and REM sleep strongly decreased or were absent whereas the EEG became isoelectric. The different states of sleep were proportional to Tbmin during prior torpor in contrary to active phases. Delta waves increased after torpor but low temperatures did not induce greater delta power compared to higher temperatures. Ours results showed that temperature was a determining factor for the quality and quantity of sleep. Low temperatures might be inconsistent with the recovery function of sleep. Heterothermy caused a sleep debt thus there was a rebound of sleep at the beginning of euthermia to compensate the lack of sleep.